The growth and spread of large-scale assessments and test-based accountabilities: a political sociology of global education reforms. Issue 1 (2nd January 2019) - Verger, Antoni; Parcerisa, Lluís; Fontdevila, Clara
ABSTRACT: The Global Education Reform Movement (GERM) is expanding internationally and reaching countries that seemed to be immune to this education reform approach until quite recently. Accordingly, more and more educational systems in the world are articulated around three main policy principles: accountability, standards and decentralisation. National large-scale assessments (NLSAs) are a core component of the GERM; these assessments are increasingly used for accountability purposes as well as to ensure that schools achieve and promote centrally defined and evaluable learning standards. In this paper, we explore these trends on the basis of a new and original database on NLSAs, as well as on data coming from the Programme for International Student Assessment (PISA) questionnaires. In the paper we also discuss how different theories on policy dissemination/globalisation explain the international spread of NLSAs and test-based accountability worldwide, and reflect on the potential of a political sociology approach to analyse this globalising phenomenon.